Joint User Association and Power Allocation for Licensed and Unlicensed Spectrum in 5G Networks - Ali, Mudassar; Qaisar, Saad; Naeem, Muhamamd; Mumtaz, Shahid (GLOBECOM : proceedings : 2017 IEEE Global Communications Conference : Singapore, 4-8 December 2017, 2017)
The foresighted enormous increase in mobile traffic over the coming years will result in severe congestion on available radio spectrum. The use of additional spectrum in future fifth generation (5G) mobile networks will be inevitable. LTE-Unlicensed (LTE-U) is an evolving technology, which effectively utilizes available unlicensed spectrum to increase the capacity of unified 5G network. However LTE-U causes severe interference to existing WiFi networks, which needs to be addressed to take full advantage LTE-U. In this paper we thrive to provide a sub-optimal resource allocation for co-existing LTE-U and WiFi networks to maximize throughput and hence minimize the interference. We formulated an optimization problem for Joint User Association and Power Allocation for Licensed and Unlicensed Spectrum (JUAPALUS) with objective to maximize sum rate of LTE-U/WiFi heterogeneous network (HetNet) in multi-operator scenario, subject to minimum rate guarantee and co-channel interference threshold. We propose mesh adaptive direct search (MADS) algorithm as solution to optimization problem to obtain ε-optimal results. The performance of proposed algorithm is shown in terms of network key performance indicators (KPIs) such as throughput, number of users accommodated. We also benchmark the results from MADS against outer approximation algorithm (OAA).